مقاصد الشریعہ کا اصول فقہ میں مقام: ایک تجزیاتی مطالعہ: The Status of Maqasid al-Shariah in Usul al-Fiqh: An Analytical Study (Khairulummah, 2025)
This analytical study explores the role and significance of Maqasid al-Shari‘ah (Objectives of Islamic Law) within the framework of Usul al-Fiqh (Principles of Islamic Jurisprudence). It investigates how the higher objectives of Shari‘ah—such as the preservation of religion, life, intellect, progeny, and wealth—serve as guiding principles in the process of legal reasoning and Ijtihad. The paper traces the historical development of Maqasid within Usul, from early jurists to the monumental contributions of Imam al-Ghazali and Imam al-Shatibi. Furthermore, it highlights the practical applications of Maqasid in sources like Qiyas, Maslahah Mursalah, and Sadd al-Dhara’i. The study also critically examines the relevance of Maqasid in addressing modern legal and ethical challenges, emphasizing the need for a balance between textual fidelity and purposive reasoning. It concludes that Maqasid al-Shari‘ah is not a marginal concept but a central and dynamic force in the evolution and renewal of Islamic jurisprudence.